2010
DOI: 10.4103/0250-474x.84585
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial enzymes and sarcoplasmic ATPase in cardioprotection mediated by aqueous extract of Desmodium gangeticum (L) DC root on ischemic reperfusion injury

Abstract: The present study investigate the protective effect of aqueous root extract of Desmodium gangeticum in preserving mitochondrial and sarcoplasmic ATPase during ischemia reperfusion injury. The isolated rat hearts in both drug and control group were subjected to warm ischemia (37°), followed by reperfusion with the Langendorff perfusion system. The aqueous root extract of Desmodium gangeticum (L) at a dose of 50 mg/kg body weight was found to be effective in the rat heart for the management of ischemic reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Arsenic significantly elevated Creatine Kinase (CK) [ 62 ] and Creatine Phosphokinase (CPK) [ 68 ], which indicate stress to the heart, and elevated Creatine Kinase from muscle and brain (CK-MB) [ 70 ], as well as levels of serum troponin [ 54 ], which are cardiac markers used to diagnose acute myocardial infarction. Arsenic increased inflammation, measured with C-reactive protein (CRP) [ 63 ], and increased the activities of cardiac enzymes lactate dehydrogenase (LDH) [ 55 , 70 ], aminotransferase (AST) [ 56 ], alkaline phosphatase (ALP) [ 56 , 70 ], and aspartate aminotransferase (ALT) [ 56 , 70 ], all of which indicate necrotic damage to the heart [ 75 ]. Furthermore, arsenic caused notable changes in cardiac structures including cytoplasmic vacuolization, myofibrillar loss, and cardiomyocyte necrosis [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic significantly elevated Creatine Kinase (CK) [ 62 ] and Creatine Phosphokinase (CPK) [ 68 ], which indicate stress to the heart, and elevated Creatine Kinase from muscle and brain (CK-MB) [ 70 ], as well as levels of serum troponin [ 54 ], which are cardiac markers used to diagnose acute myocardial infarction. Arsenic increased inflammation, measured with C-reactive protein (CRP) [ 63 ], and increased the activities of cardiac enzymes lactate dehydrogenase (LDH) [ 55 , 70 ], aminotransferase (AST) [ 56 ], alkaline phosphatase (ALP) [ 56 , 70 ], and aspartate aminotransferase (ALT) [ 56 , 70 ], all of which indicate necrotic damage to the heart [ 75 ]. Furthermore, arsenic caused notable changes in cardiac structures including cytoplasmic vacuolization, myofibrillar loss, and cardiomyocyte necrosis [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed aqueous root extract improved cardiac function after ischemia reperfusion injury by mitochondrial and sarcoplasmic ATPase preservation in the myocardium. Gas chromatography-mass spectrometry and atomic absorption study of Shalaparni root extract the showed presence of bio-constituents that can activate the release of calcium in cardiac tissue (50).…”
Section: Cardiotonic Effectmentioning
confidence: 99%
“…The total antioxidant capacity of the extract was found to be 149.91 % as compared to standard ascorbic acid 87.8 %. The extract also inhibited the ferrylbipyridyl (chromogen) formation in a dose dependent fashion (IC 50 0.115 mg/ml) 33 .…”
Section: Phytochemistrymentioning
confidence: 91%